(untitled) (KYAMC Journal, 2017)
The practice of anesthesia has changed dramatically since the days of John Snow. The modern anaesthesiologist is now both a consultant and a primary care provider. The consultant role is appropriate because the primary goal of the anesthetist- to see the patient and comfortably through surgery- generally takes only a short time. However, because anaesthesiologist manage all "noncutting" aspects of the patient’s care in the immediate perioperative period, they are also primary care providers. The "Captain of the ship"doctrin, which held the surgeon responsible for every aspects of the patient’s perioperative care is no longer valid. The surgeon and anesthesiologist must function together effectively, but both are ultimately answerable to the patient rather than to each other. Patient can select their own anesthesiologist, as well as the surgeon. On the other hand an anesthesiologists have every rights to choice a surgeon, or refuse giving anesthesia to a certain patients. The practice of anesthesia is no longer limited to the operating room. The anesthesiologist are now routinely asked to monitor, sedate and provide general or regional anesthesia outside the operation room. Anesthesiologist have traditionally been pioneers in cardiopulmonary resuscitation and continue to be integral members of resuscitation team. Preoperative evaluation of patients, perioperative and postoperative monitoring and care is absolutely essential. Surgeon-anesthesiologist, anesthesiologist-patient rapport/ co-ordination should be maintained. Documentation is important for both quality assurance and medico legal purpose. Preoperative and intraoperative anesthetic record must be preserved as it serves many purposes. This record should as pertinent and accurate as possible. The written consent with a witness must be taken. The postoperative notes are also essential as many of the patients files complaint against the anesthesiologist, surgeon, and hospitals. Therefore, there are no alternatives rather to preserve all sorts of written documents for their own safety. KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 806-809